Ministry of Petroleum and Mineral Resources Decrees Nos. 1760, 1761 And 1762 Of The Year 2024 = وزارة البترول والثروة المعدنية قرارات رقم 1760 و1761 و1762 لسنة 2024 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic